Implementation of Culturally Responsive Teaching as a Reinforcement for Prospective Chinese Language Teachers to be Adaptive and Responsive - Irawati, Retno Purnama; Pamuji, Dian Yuni; Agwinanda, Almira; Anggraeni, Anggraeni (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
The graduate profile of the Chinese Language Education Study Program aims to produce Chinese language teachers who can both teach and conduct research on Chinese language learning issues. Culturally responsive teaching is a method for developing adaptive and responsive educators. Chinese language teachers who are culturally responsive will be able to connect Chinese culture with students' backgrounds and create meaningful learning by utilizing cultural knowledge and students' learning styles. This research aims to analyse the distribution of courses in the Chinese Language Education curriculum in Indonesia that adopt culturally responsive teaching; identify the implementation of culturally responsive teaching for strengthening prospective Chinese language teachers; and explain the factors hindering and supporting the success of culturally responsive teaching for strengthening prospective Chinese teachers. The research method used is qualitative research, utilizing an observational descriptive qualitative approach. The study was conducted to systematically describe the phenomenon of culturally responsive teaching based on factual data. Data collection techniques include literature review, documentation, observation, questionnaires, and interviews. The results of this study show that the Chinese Language Education programs in Indonesia have adopted culturally responsive teaching in their curricula, both in education-focused and non-education-focused programs. This implementation helps prospective teachers understand the relationship between language and culture, although various challenges remain, such as a lack of training, limited resources, negative attitudes, and high workloads. However, success is also evident through teacher commitment and interest, institutional support, integrated curriculum, technology and learning media use, and interdisciplinary approaches. With continuous evaluation and proper support, culturally responsive teaching has the potential to further enhance the competencies of prospective Chinese language teachers in implementing culturally responsive teaching.